Are anti-ganglioside antibodies detectable in serum from patients with critical illness myopathy and polyneuropathy? (Revista Médica de Trujillo, 2020)
Introduction: Critical illness myopathy (CIM) and polyneuropathy (CIP) are the most common cause of acquired weakness in intensive care units (ICU). However, its exact pathogenesis remains unclear. Abnormal excitability of muscle due to a sodium channelopathy is one of the mechanisms proposed. The aim of this study is to test for the presence of anti-ganglioside antibodies in serum from patients with CIM or both combined CIM/CIP, since there is evidence that they can cause reversible dysfunction of voltage-gated sodium channels.Methods: In a prospective way, we studied 35 patients admitted in ICU by weekly EMG. When positive spontaneous activity (PSA) was detected, a muscle biopsy was performed. Twenty patients met criteria of CIM; five of them also developed overlapping CIP. We did not detect any kind of abnormality in 10 patients during the follow up period. Sera were analyzed for the presence of anti-ganglioside antibodies (Ganglioside-profile 2 Euroline, Euroimmun). Results: Overall, positive reactivity against anti-GT1b was found in one patient with CIM, representing 2.8% (1/35) of the total sample.Conclusion: Reduced percentage of patients affected of CIM or CIM/CIP exhibits positive reactive against anti-ganglioside antibodies. Thus, it could be suggested they do not play a primary role in their pathogenesis. Key words: Critical illness myopathy, critical illness polineuropathy, difficult weaning, channelopathy, muscle fiber inexcitability, anti-ganglioside antibodies  DOI: http://dx.doi.org/10.17268/rmt.2020.v15i01.04